THE INTERACTION BETWEEN THE EDUCATIONAL INSTITUTION AND THE FAMILY IN THE DEVELOPMENT OF A CHILD'S SPEECH (International journal of artificial intelligence, 2025)
The new concept of the relationship between the family and the preschool educational institution is based on the idea that parents are responsible for the upbringing of children, and all other social institutions are called upon to help them, support, guide them, and complement their educational activities. The policy of transforming education from family to public education, which is officially implemented in our country, is becoming a thing of the past.